Investigation into Breast Cancer and Partial Breast Reconstruction: A Review - Mohammad Reza Ebadi; Maryam Kazemi Aghdam; Zeinab Safarpour Lima; Ladan Younesi (PAGEPress Publications, 2019)
Growing increasingly in South America, Africa and Asia, breast cancer is known as the dominant type of cancer in women. Different treatments are available for breast cancer, among which surgery is the most widely used, but researchers are trying to develop new strategies. One of the most prominent surgical methods is referred to as oncoplastic surgery, that helps to remove segments of malignant breast tissue. This type of surgery aims to obtain vast surgical margins, while the remaining tissue is rearranged so that the better cosmetic outcome is obtained. This review will investigate the breast cancer and then discuss partial breast reconstruction. Before outlining the procedures, the different types of partial breast reconstruction will be discussed. Finally, advantages and disadvantages will be outlined. MEDLINE database was used to conduct the search. The main terms used were 'Conservation Breast Surgery Reconstruction' AND 'Oncoplastic Surgery', 'Partial Mastectomy Reconstruction' AND 'Conservative Breast Surgery Reconstruction', 'oncoplastic' [All Fields], 'breast' AND 'surgery' OR 'surgery' operative', 'oncoplastic' ('breast')'. The bibliographies of relevant papers were manually searched up to October 2018, but more recent voices are also included.